Extraction of Phenolic Compounds From Hazelnut Shell Waste - Şengün, Duygu; Yüksel Özşen, Aslı (Izmir Institute of Technology, 2018)
The main objective of this study is to obtain phenolic compounds from hazelnut shell waste by extraction and to add value to hazelnut shell wastes. Soxhlet extraction, ultrasonic extraction and combined extraction (soxhlet followed by ultrasonic extraction) methods were used for the extraction of hazelnut shell to obtain phenolic and antioxidant compounds. The effect of extracting solvent (ethanol, methanol, n-hexane, acetone and chloroform), extraction time (8h, 2 cycle and 3 cycle) (1 cycle = 20 min for hexane, 25 min for chloroform, 40 min for ethanol, 45 min for methanol and 35 min for acetone), solid-liquid ratio (4, 8 and 12 g / 250 ml) and size of hazelnut shell (1 mm and 2 mm) were investigated on the phenolic content and antioxidant capacity. Gas Chromatography equipped with a Mass Spectrometry (GC-MS) was used for the analysis of liquid products obtained from the extraction of hazelnut shell. Palmitic acid and oleic acid variations were detected at high ratios. The combined extraction method, which was composed of soxhlet and ultrasonic extractions, resulted in a significant increase in the yield of extraction. Also, higher yield was obtained from methanol and ethanol extraction because of the higher polarity of the solvents. On the other hand, it was observed that there was no significant effect of the extraction time on the extraction yield. The highest phenolic content was 0.166 mg gallic acid equivalent/ml and this value was obtained with methanol by combined extraction using 4 g hazelnut shell and 250 ml solvent.

Bu çalışmanın esas amacı fındık kabuğu atığından ekstraksiyon yöntemi ile fenolik bileşenler elde etmek ve fındık kabuğu atıklarının değerlendirilmesini sağlamaktır. Fenolik ve antioksidan bileşenlerin eldesinde sokslet ekstraksiyonu, ultrasonik ekstraksiyon ve bu iki ekstraksiyon yönteminin birleşmesinden oluşan kombine ekstraksiyon yöntemi kullanılmaktadır. Çeşitli çözgen tiplerinin (n-hekzan, kloroform, etanol, metanol ve aseton), ekstraksiyon süresinin (2 döngü (1 döngü=hekzan için 20 dk, kloroform için 25 dk, etanol için 40 dk, metanol için 45 dk ve aseton için 35 dk), 3 döngü ve 8 saat), katı sıvı oranın (4, 8 ve 12 g fındık kabuğu/ 250 ml çözgen) ve fındık kabuğu boyutunun (1 mm ve 2 mm) fenolik ve antioksidan bileşenler üzerindeki etkisi incelenmektedir. Fındık kabuğu ekstraksiyonundan elde edilen sıvı ürün analizinde Gaz Kromatogram-Kütle Spektrometri (GC-MS) kullanılmış, yüksek oranda palmitik asit ve oleik asit varyasyonları tespit edilmiştir. Sokslet ve ultrasonik ekstraksiyonların birleşiminden oluşan kombine ekstraksiyon yöntemi, ekstraksiyon veriminde önemli bir artışa sebep olmuştur. Ayrıca metanol ve etanol çözgenlerinin polaritesinin yüksek olması fındık kabuğundan daha fazla verim elde edilmesini sağlamıştır. Öte yandan, ekstraksiyon süresinin verime ciddi bir etkisinin olmadığı gözlemlenmiştir. En yüksek fenolik bileşen değeri metanol kombine ekstraksiyonunda 4 g fındık kabuğu ve 250 ml çözgen kullanılarak 0.166 mgGAE/ml elde edilmiştir.
Fenolik Bileşenlerin Fındık Kabuğu Atıklarından Ekstraksiyonu
Thesis (Master)--Izmir Institute of Technology, Chemical Engineering, Izmir, 2018
Full text release delayed at author's request until 2019.02.02
Includes bibliographical references (leaves: 55-61)
Text in English; Abstract: Turkish and English
Keywords: Hazelnut shell; Phenolic compounds; Hazelnut shell wastes